Oil Palm Wastes And Sewage Sludge Composts As Potting Media For Chrysanthemum - Ramahsamay, Kala Devi (2008)
The use of oil palm wastes, particularly the empty fruit bunch (EFB), frond and trunk as compost are now receiving greater attention by researchers. Another organic waste that needs to be disposed off in Malaysia is sewage sludge. This research is important in reducing waste management problem and conserve plant nutrients. Therefore the objective of this study was to determine the optimum blend of oil palm wastes (EFB, frond and trunk) and sewage sludge that will produce a compost physically similar to peat which can be used as potting media. Analysis of samples of sewage sludges collected from ten different Indah Water Consortium treatment plants in Peninsular Malaysia, showed that the chemical characteristics of the sludges varied greatly, i.e. 6.13 to 57.67% C, pH water 3.57 to 6.43, 0.68 to 2.90% total N, 0.24 to 1.62% P, C/N ratio 4.13 to 37.94, 112 to 2902 mg.kg-1 Mg, 401 to 1209 mg.kg-1 K, and 0.16 to 2.16% Ca. The concentrations of heavy metals in sludges also varied greatly, i.e. 36 to 308 mg.kg-1 Pb, 0.51 to 6.49 mg.kg-1 Cd, 63 to 732 mg.kg-1 Cu, 32 to 420 mg.kg-1 Mn, 10 to 151 mg.kg-1 Ni, 1.22 to 4.01% Fe and 153 to 7012 mg.kg-1 Zn. Sewage sludges produced by Indah Water Konsortium (IWK) has low levels of heavy metals (except for Zn) and may be used on ornamental plants but caution should be taken for plants that are sensitive to Zn. A study on composting different oil palm wastes with sewage sludge was carried out on a small scale in the glasshouse by using a polystyrene box. Shredded oil palm wastes (EFB, frond and trunk) were mixed with sewage sludge in different ratios (100:0, 3:1 and 4:1 ratio) and moistened to 50 % moisture content. Based on the temperature, C/N, NH4+-N and NO3- - N + NO2- -N patterns of the oil palm wastes-sludge blends during 12 weeks composting, all EFB, frond and trunk with added sludge composts seemed to perform similarly. After 12 weeks of composting, the trunk composts had finer particle size, similar to peat, compared to the other composts. However, the EFB-sludge and frond-sludge composts still contained long strands of fibres. These composts may need to be composted for more than 12 weeks to achieve finer particle size. The trunk:sludge (4:1) compost was selected to be the best compost in terms of particle size, colour, nutrient and heavy metals content. It had 2.05 % total N, pHwater 6.2, 18.96 C/N ratio, 0.71% Ca, 0.64% P, 1.39% K, 0.23% Mg and heavy metals concentrations of 26.30 mg.kg-1 Pb, 671 mg.kg-1 Zn, 6306 mg.kg-1 Fe, 91.93 mg.kg-1 Mn, 1.63 mg.kg-1 Cd and 68.83 mg.kg-1 Cu, which is within the recommended levels of Council of European Communities guidelines, CEC (1986) in compost. When the trunk:sludge (4:1) compost was tested with potted chrysanthemum, plants grown in compost and compost:peat (3:1 v/v) potting media had good vegetative growth (top dry matter weight and total leaf area) and other flowering qualities (earlier appearance of first visible bud/flower and higher number of bloomed flowers) which are suitable for sale than the standard peat medium. The growth of chrysanthemum was influenced by the addition of fertilizers. The use of the compost with only slow release fertilizer, agroblend, was found to be sufficient to produce good plant growth of flowers per pot. Thus this would decrease the cost of fertilizer and labour. On the whole the growth performance of compost and compost:peat (3:1 v/v) growth medium were similar. Therefore, this study showed that composted oil palm trunk-sewage sludge has the potential to be used as a soilless potting medium for chrysanthemum, i.e as a substitute for peat. This may convert oil palm waste into a value-added product and provide an alternative disposal method for sewage sludge produced by IWK.